Curious George at the parade - Rey, Margret; Rey, H. A. 1898-1977 (Hans Augusto); Vipah Interactive (Boston, Mass. : Houghton Mifflin, 1999)
George's curiosity creates chaos at a holiday parade.
Keywords: Monkeys -- Fiction; Parades -- Fiction